(untitled) (MCIT: Proceedings of International scientific and practical conference, 2020)
The explosive process influence on the environment with the existing impenetrable fixed inclusion is investigated by quasiconformal mappings numerical methods and step-by-step parameterization of the environment and the process characteristics numerical methods. The boundaries of the crater formed by the explosion, pressed and undisturbed areas of soil are determined. Numerical experiments were performed on the basis of the developed algorithm